IMPACT OF SERVICE LEADERSHP, REWARDING EMPLOYEE PERFOMANCE WTH JOB SATISFACTION AS AN INTERMEDIATE VARIABLE ( STUDY ON ECONOMIC ORGANIZATION EMPLOYEES IN CENTRAL JAVA ) - Eldes Willy Filatrovi (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
The cause of this have a look at changed into to identify and look at the effect of servant management, compensation, and process pleasure as intervening variables on worker performance. The populace of this have a look at changed into financial institution personnel in Central Java. The populace of this have a look at is running in banks in Central Java. The pattern for this survey consisted of one hundred respondents. Samples have been received primarily based totally on easy random sampling. SEM-AMOS changed into used because the information evaluation approach on this have a look at. The result is that praise no longer affects performance, process enjoyment definitely affects performance, servant management definitely affects performance, and praise definitely affects process enjoyment. This shows that servant management has a positive impact on work. joy. Keywords: Servant Leadership, Compensation, Job Satisfaction, Banker Performance